Human antibody response to Campylobacter jejuni flagellin protein and a synthetic N-terminal flagellin peptide. - Nachamkin, I (1989)
We measured isotype-specific human antibodies directed against Campylobacter jejuni native flagellin and a synthetic peptide derived from the N-terminal amino acid sequence of the protein by using a microdilution enzyme-linked immunosorbent assay (ELISA). Serum samples from patients with gastrointestinal infection caused by C. jejuni (n = 20) and control samples (number from normal subjects = 20; number from patients with diarrhea other than campylobacter = 20) were tested in this assay. Serum specimens from patients with campylobacter infection showed statistically significant higher isotype-specific antiflagellin antibody titers than control samples did. Detection of immunoglobulin G (IgG) antibodies was less specific (70%) than detection of either IgA or IgM antibodies in infected patients (95%). The sensitivity of testing for any of the isotypes ranged from 64 to 100% in acute-phase serum specimens and 85 to 95% in convalescent-phase serum specimens. An ELISA with an N-terminal synthetic peptide derived from the flagellin protein as antigen was not sensitive (60%) for detecting campylobacter infection but was very specific (97.5%). In conclusion, detection of serum IgA or IgM against C. jejuni flagellin may be a useful marker of infection. Although the N-terminal synthetic peptide was antigenic in a few patients with infection and showed good specificity in the ELISA, additional amino acid sequences with better sensitivity for detecting infection need to be identified.